Terapi Kognitif Efektif Meningkatkan Konsep Diri Mahasiswa dalam Menghadapi Resesi Ekonomi Pasca Pandemi Covid 19 - Laela, Sri; Hartati, Suryani (Universitas Malahayati, 2024)
ABSTRACT Students are at risk of experiencing self-concept disorders as a result of their families being affected by the Covid-19 pandemic which has caused an economic recession. An economic recession occurred marked by a weakening of the global economy, high unemployment rates, due to massive layoffs by companies, a decline in exports and investment as well as a decline in state revenues from taxes and a lowering of economic growth targets by the government. Self-concept disorders experienced by students such as: shame, lack of self-confidence and feeling like a burden on the family will certainly affect students' academic achievement. The aim of this research is to identify the effect of cognitive therapy on students' self-concept in facing the economic recession after the Covid-19 pandemic. The methodology used was a quasi-experiment one group with pretest - posttest design using a consecutive sampling method. The respondents were 27 students Academy of Nursing Hermina Manggala Husada. The research was conducted from August to January 2024. The questionnaire was used a self-concept questionnaire consisting of 30 statements. The research results show that cognitive therapy is able to improve students' self-concept in dealing with the economic recession after the Covid-19 pandemic. In conclusion, Cognitive therapy is recommended to overcome students' self-concept problems.) Keywords: Self-Concept, Students, Cognitive Therapy ABSTRAK Mahasisiwa beresiko mengalami gangguan konsep diri sebagai akibat dari keluarga yang terkena dampak pandemic covid 19 yang menyebabkan resesi ekonomi. Resesi ekonomi terjadi ditandai dengan pelemahan ekonomi global, tingginya angka pengangguran, karena PHK besar – besaran oleh perusahaan, turunnya ekspor dan investasi serta penurunan penerimaan negara dari pajak serta diturunkannya target pertumbuhan ekonomi oleh pemerintah. Gangguan konsep diri yang di alami oleh mahasiswa seperti : malu, tidak percaya diri dan merasa menjadi beban keluarga tentunya akan mempengaruhi prestasi akademik mahasiswa. Tujuan penelitian ini adalah mengidentifikasi pengaruh terapi kognitif terhadap konsep diri mahasiswa dalam menghadapi resesi ekonomi pasca pandemic covid 19. Metodologi yang digunakan quasi-experiment one group with pretest – posttest design dengan metode consecutive sampling. Responden berjumlah 27 mahasiswa Akper Hermina Manggala Husada. Penelitian dilakukan Agustus sampai Januari 2024. Kuesioner yang di gunakan adalah kuesioner konsep diri yang terdiri dari 30 pernyataan. Hasil penelitian menunjukan bahwa terapi kognitif mampu meningkatkan konsep diri mahasiswa dalam mengadapi resesi ekonomi pasca pandemic covid 19. Kesimpulannya Terapi kognitif di rekomendasikan untuk mengatasi masalah konsep diri mahasiswa. Kata Kunci: Konsep Diri, Mahasiswa, Terapi Kognitif